The Effects of Modified Lymphoscintigraphy Techniques on Sentinel Lymph Node Biopsy Success During the COVID-19 Pandemic Period - Cemil Yüksel; Serdar Çulcu; Lütfi Doğan (Journal of Investigative Surgery, 2022)
Background and objective Sampling of the sentinel lymph node (SLN) in breast cancer provides accurate information about the condition of the axilla in 95% of cases. Technically in detecting SLN; radioactive substance, dyers or both are used. During the COVID-19 (Coronavirus disease 2019) pandemic, delayed images were not taken in lymphoscintigraphy to reduce the risk of transmission by shortening the waiting time in our center. In this study, the effects of early and delayed lymphoscintigraphic images and only early images on our clinical practice were evaluated. Methods We investigated the data of 147 patients in this study who underwent SLNB due to early-stage breast cancer at our institute during the COVID-19 pandemic period (PP) (March/April/May 2020) and within 3 months before the pandemic were evaluated. Results Patients were divided into two groups, before pandemic (BP) and PP. BP consisted of patients whose early and delayed images were taken in lymphoscintigraphy whereas PP consisted of those with early images only. There were 74 patients in the BP group and 73 patients in the PP group. Early phase increased uptake was not observed in 23 patients, and increased uptake was obtained from 22 of these patients with delayed imaging in BP period. In PP, increased uptake was not observed in 12 patients. SLN was not detected in 2 patients in the BP group and 7 in the PP group. It was found that the sensitivity, NPV and accuracy of the SLNB procedure performed after taking delayed images was higher. Conclusions In the present study, we believe that if technically possible, delayed images taken during the lymphoscintigraphy can assist the surgeon in terms of SLN detection and the number of SLNs removed.